An Experience of Donor Lymphocyte Infusion after Reduced-Intensity Conditioning Allogeneic Hematopoietic Stem Cell Transplantation for Chronic Granulomatous Disease - Tahereh Rostami; Azadeh Kiumarsi (MDPI AG, 2020)
Allogeneic hematopoietic stem-cell transplantation is a well-known curative treatment for patients with chronic granulomatous disease. We present our experiment regarding ten patients with chronic granulomatous disease who underwent a reduced intensity conditioning regimen consisting of melfalan, fludarabine, and antithymocyte globulin. Donor lymphocyte infusion was used in three representative patients who developed mixed donor chimerism. After at least 2 years of median follow-up, 8 of the 10 patients are alive and well.